2019
DOI: 10.1038/s41419-019-1429-0
|View full text |Cite
|
Sign up to set email alerts
|

Potassium channel activity controls breast cancer metastasis by affecting β-catenin signaling

Abstract: Potassium ion channels are critical in the regulation of cell motility. The acquisition of cell motility is an essential parameter of cancer metastasis. However, the role of K+ channels in cancer metastasis has been poorly studied. High expression of the hG1 gene, which encodes for Kv11.1 channel associates with good prognosis in estrogen receptor-negative breast cancer (BC). We evaluated the efficacy of the Kv11.1 activator NS1643 in arresting metastasis in a triple negative breast cancer (TNBC) mouse model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 77 publications
1
69
1
Order By: Relevance
“…Moreover, considering all the molecular subtypes it emerged that patients with high Kv11.1 protein expression have a longer Progression-Free Survival and the same trend was observed for Local Relapse Free-Survival and Metastases-Free Survival (Iorio et al, 2018). A recent meta-analysis focused on KCNH2 gene expression confirmed our data, showing that high expression of the gene was associated with longer relapse-free survival (Breuer et al, 2019) and more interestingly, the association was restricted to ER-negative patients. The inward rectifier Kir3.1 (also named KCNJ3) encoded by KCNJ3 gene, is positively associated with the development of nodal metastases (Stringer et al, 2001).…”
Section: Kcnn4supporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, considering all the molecular subtypes it emerged that patients with high Kv11.1 protein expression have a longer Progression-Free Survival and the same trend was observed for Local Relapse Free-Survival and Metastases-Free Survival (Iorio et al, 2018). A recent meta-analysis focused on KCNH2 gene expression confirmed our data, showing that high expression of the gene was associated with longer relapse-free survival (Breuer et al, 2019) and more interestingly, the association was restricted to ER-negative patients. The inward rectifier Kir3.1 (also named KCNJ3) encoded by KCNJ3 gene, is positively associated with the development of nodal metastases (Stringer et al, 2001).…”
Section: Kcnn4supporting
confidence: 85%
“…Another paper from the same group confirmed such evidences in vivo, in MCF-7 xenografts and also determined that the mechanism underlying tumor growth inhibition was centered on a Kv11.1-mir328 pathway (Wang et al, 2015). Recently it was shown that small molecule activators of the Kv11.1 channel impair tumor growth and metastasis in xenografts of TNBC (Breuer et al, 2019).…”
Section: Potassium Channels As Therapeutic Targetsmentioning
confidence: 79%
“…As some ion channels are expressed with temporal and tissue specificity, endogenous spatiotemporal gradients of V mem can be generated across tissues and organs (1). Consistent with this, changes in V mem are known to influence embryonic development, among other processes (2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 82%
“…Therefore, Kv11.1 inhibits TNBC cell proliferation by activating a cellular senescence program [98]. Breuer et al confirmed that NS1643 reprograms the EMT by attenuating the Wnt/β-catenin signaling pathway, inhibits cancer cell stemness, and significantly reduces the metastatic spread of breast tumors in a MDA-MB-231 mouse model [99]. Regardless, cardiotoxicity is an important limiting factor for potential therapeutic molecules acting on Kv11.1.…”
Section: K + Channelsmentioning
confidence: 99%